FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS BONTOBAHARI KABUPATEN BULUKUMBA - Iramaya Sari; Aldina Lestari (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2019)
Asi is an ideal source of nutrition with a balanced composition and adapted to the needs of baby's growth. The purpose of this study was exclusive breastfeeding factors in primipara postpartum mothers in the Bonto Bahari Community Health Center work area. The design of this study employs analytical design with a cross-functional approach. The total population and sample in this study were 30 respondents using total sampling. The data collection method used is the questionnaire sheet. From the results of the research, it was found that the respondents' characteristics were seen from the age of the majority of respondents aged 20-35 years as many as 28 respondents, and the majority of respondents had an elementary education level of 11 respondents. % and most respondents have a high cultural influence of 70.0% while for health support some respondents have good health personnel support of 76.7% and most respondents do not provide breast milk to their babies at 86.7% while biavariate analysis by using Fisher's alternative chi square statistical test. The results showed that the level of knowledge (p = 0.008) and cultural influence (p = 0.005) had a significant relationship with exclusive breastfeeding while the support of health workers (p = 1,000) did not have an association with exclusive breastfeeding. In order for this study to provide information about exclusive breastfeeding, especially postpartum mothers and become input for health workers in the area of ​​Gattareng Health Center and also useful for all parties and can be a reference for future research